PREPARATION AND CHARACTERIZATION OF CHITOSAN VANILINE AS ELECTROLYTE POLYMER MEMBRANE - Pramono, Edi; Asiska Prabowo, Pandu Satrio; Purnawan, Candra; Wulansari, Jati (Alchemy Jurnal Penelitian Kimia, 2012)
The research of chitosan modification with vanilin and its characterization as polymer electrolyte membranes was carried out. Chitosan-based shciff base compounds was synthesizedÂ  from chitosan and vanilin with pyperidine as catalyst. The polymers were characterized by Fourier Transform Infrared (FTIR) and its cationic exchange capacity, while membranes were characterized by cationic exchange capacity, swelling degree and its thermal stability. The existence of imine vibration peak provides that the chitosan vaniline was succesfully synthesized. The addition of vanillin increases the cationic exchange capasity of membrane, however it decreases the swelling degree. Thermal data indicate the polymer membrane degraded above 250oC with three step degradation. Based on the cationic exchange capacity and its thermal stability, the membrane has a good potential for application in polymer electrolyte membrane fuel cells, but modifications are still needed to reduce the swelling degree of membrane.